Strategi Pemerintah dalam Pemberantasan Demam Berdarah Dengue (DBD) di Kota Jambi - Susianti, Novia (Jurnal Bina Praja, 2017)
The mortality rate and the distribution of dengue fever case in Indonesia tend to increase. Jambi Province is the province with the highest mortality rate in Indonesia in 2013, and Jambi City is the highest contributor for the last 3 years. Eradication efforts have been made, but they have not been able to break the chain of transmission. This research uses descriptive design with a qualitative approach to identify the causes of inaccuracy of eradication efforts and to determine the strategy of eradicating dengue fever in Jambi City. Site selection was done by purposive sampling, with the highest incidence rate criterion in 2015. The informants were chosen based on the criteria of conformity and adequacy, covering the Health Department, the Puskesmas, the sub-district and the community i.e. the larva monitoring cadre (jumantik). The assessment scheme is based on government policy implementation scheme in eradicating DHF by the identification of factors based on ultrasound analysis (Urgency, Serious, Growth). The strategy of eradication efforts is based on SWOT analysis (Strength, Weaknesses, Opportunities, Threats). The determination of alternative strategies was chosen based on Mc. Namara's screening theory, with 5 criteria of effectiveness, ease, benefits, time, and cost. The result of the research shows that the inaccuracy of dengue eradication efforts in Jambi City lies in the ineffectiveness of the implementation of the Mosquito Nest Eradication (PSN) movement through cross-sector integration in community empowerment routinely and independently. The main strategy that can be done by the government is to increase the role of larva monitoring cadres and larva monitoring students (sismantik) through budget support from across sectors in campaigning PSN movement regularly, either at house or institution environment.